Influence of foliar application of plant growth regulators on quality of guava in winter season crop (Indian Journal of Arid Horticulture, 2025)
Foliar spray of NAA (20, 40 and 60 ppm), 2, 4-D (10,15 and 20 ppm) and GA, (30, 60 and 90 ppm) was done on guava trees of cultivar 'Sardar' at fruit setting stage and repeated after one month. The chemical characteristics like T. S. S., reducing sugar, non-reducing sugar and total sugar were recorded maximum in treatment with NAA at 60 ppm viz. 15.45%, 4.56%, 3.12% and 7.84%, respectively. The minimum acidity of 0.395 % was also recorded in the same treatment. Whereas, the mean maximum ascorbic acid and pectin content were recorded in treatment with GA, at 90 ppm viz., 205.16 mg/100 g pulp and 0.80%, respectively
Keywords: Growth regulators; guava; chemical characterestics